2004
DOI: 10.1007/s00426-004-0195-4
|View full text |Cite
|
Sign up to set email alerts
|

Perceived duration of expected and unexpected stimuli

Abstract: Three experiments assessed whether perceived stimulus duration depends on whether participants process an expected or an unexpected visual stimulus. Participants compared the duration of a constant standard stimulus with a variable comparison stimulus. Changes in expectancy were induced by presenting one type of comparison more frequently than another type. Experiment 1 used standard durations of 100 and 400 ms, and Experiments 2 and 3 durations of 400 and 800 ms. Stimulus frequency did not affect perceived du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
129
6

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 109 publications
(147 citation statements)
references
References 63 publications
(86 reference statements)
12
129
6
Order By: Relevance
“…IOR has been shown to have a spatial gradient, being strongest at the attended location and decreasing in magnitude with visual distance (Bennett & Pratt, 2001). Earlier studies on duration perception have shown that attended stimuli are perceived as having a longer duration compared to unattended stimuli or stimuli that receive less attention (Block, Hancock, & Zakay, 2010;Tse, Intriligator, Rivest, & Cavanagh, 2004;Ulrich, Nitschke, & Rammsayer, 2006). In our study, participants were presented with four top-up stimuli at the adapted location followed by the cross-modal duration judgment task, with the visual test stimulus being presented between 1000 and 2000 ms after the last top-up.…”
Section: Discussionmentioning
confidence: 99%
“…IOR has been shown to have a spatial gradient, being strongest at the attended location and decreasing in magnitude with visual distance (Bennett & Pratt, 2001). Earlier studies on duration perception have shown that attended stimuli are perceived as having a longer duration compared to unattended stimuli or stimuli that receive less attention (Block, Hancock, & Zakay, 2010;Tse, Intriligator, Rivest, & Cavanagh, 2004;Ulrich, Nitschke, & Rammsayer, 2006). In our study, participants were presented with four top-up stimuli at the adapted location followed by the cross-modal duration judgment task, with the visual test stimulus being presented between 1000 and 2000 ms after the last top-up.…”
Section: Discussionmentioning
confidence: 99%
“…2 Consistent with a possible influence of dynamic attending on auditory perception, several other ERP studies have found enhanced brain responses to auditory stimuli when they occurred at attended moments (Lange, Krämer, & Röder, 2006;Lange, Rösler, & Röder, 2003;Sanders & Astheimer, 2008). An advantage in pitch processing of temporally expected tones has also been reported (Bausenhart, Rolke, & Ulrich, 2007;Jones, Moynihan, MacKenzie, & Puente, 2002), and attended events often seem longer in duration than do unattended events (K.-M. Chen & Yeh, 2009;Mattes & Ulrich, 1998;Tse, Intriligator, Rivest, & Cavanagh, 2004;Ulrich, Nitschke, & Rammsayer, 2006). Although these studies compared expected with unexpected events, rather than metrically accented and unaccented events, within the dynamic attending framework the former can be considered to be more strongly expected than the latter (Large & Palmer, 2002).…”
Section: The Present Studymentioning
confidence: 91%
“…Such an asymmetric arrangement of comparison durations can result in the so-called asymmetry effect (Guilford 1954) and thus artificially inflate the size of the OE. Accordingly, Seifried and Ulrich (2010) observed smaller OEs of approximately 5 % when comparison durations were arranged symmetrically around the standard duration.An OE has also been observed in a modified paradigm, in which two successive stimuli were presented in each trial (Ulrich et al 2006). In this paradigm, a visual standard stimulus of constant duration always preceded a visual target stimulus of varying duration.…”
mentioning
confidence: 98%
“…An OE has also been observed in a modified paradigm, in which two successive stimuli were presented in each trial (Ulrich et al 2006). In this paradigm, a visual standard stimulus of constant duration always preceded a visual target stimulus of varying duration.…”
mentioning
confidence: 98%